Anhydrous Nucleic Acid Nanoparticles for Storage and Handling at Broad Range of Temperatures. Issue 13 (6th February 2022) - Tran, Allison N.; Chandler, Morgan; Halman, Justin; Beasock, Damian; Fessler, Adam; McKeough, Riley Q.; Lam, Phuong Anh; Furr, Daniel P.; Wang, Jian; Cedrone, Edward; Dobrovolskaia, Marina A.; Dokholyan, Nikolay V.; et al.
Abstract: Recent advances in nanotechnology now allow for the methodical implementation of therapeutic nucleic acids (TNAs) into modular nucleic acid nanoparticles (NANPs) with tunable physicochemical properties which can match the desired biological effects, provide uniformity, and regulate the delivery of multiple TNAs for combinatorial therapy. Despite the potential of novel NANPs, the maintenance of their structural integrity during storage and shipping remains a vital issue that impedes their broader applications. Cold chain storage is required to maintain the potency of NANPs in the liquid phase, which greatly increases transportation costs. To promote long‐term storage and retention of biological activities at higher temperatures (e.g., +50 °C), a panel of representative NANPs is first exposed to three different drying mechanisms—vacuum concentration (SpeedVac), lyophilization (Lyo), and light‐assisted drying (LAD)—and then rehydrated and analyzed. While SpeedVac primarily operates using heat, Lyo avoids temperature increases by taking advantage of pressure reduction and LAD involves a near‐infrared laser for uniform drying in the presence of trehalose. This work compares and defines refinements crucial in formulating an optimal strategy for producing stable, fully functional NANPs and presents a forward advancement in their development for clinical applications. Abstract : Rationally designed nucleic acids have experienced success in various applications. To study the best practices for maintaining their structural integrity over a longer time, an analysis of representative nucleic acid nanoparticles (NANPs) dehydrated via vacuum concentration, lyophilization, and light‐assisted drying, is presented. This work is a forward advancement in formulating optimal strategies for handling NANPs at broad range of temperatures.